2022
DOI: 10.1177/00084174221129941
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Occupational Therapy Camp for Children with Regulation/Sensory Processing Differences: Preliminary Evaluation

Abstract: Background. Integration of occupational therapy into a camp environment may support participation for children with neurodevelopmental differences, but evidence is limited. Purpose. This study examines the effects of participation of children with regulation/sensory processing differences at one such integrated camp on parent-established functional goals. Method. We used a pre-test/post-test repeated measures cohort design. Individualized goals were established with parents three months before camp using the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Although it did not reach statistical significance, this difference tended to increase over time, and improvements in post-test are attributed to the effect of the interventions themselves. This finding is consistent with previous work showing that intervention to improve EF has positive outcomes [13,14,[16][17][18][19] or, in any case, is correlated with them. Contrary to our hypothesis, the VMI skills improved to a similar extent between the two groups, although there was a statistically significant improvement within both groups in all outcome measures and high effect size.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although it did not reach statistical significance, this difference tended to increase over time, and improvements in post-test are attributed to the effect of the interventions themselves. This finding is consistent with previous work showing that intervention to improve EF has positive outcomes [13,14,[16][17][18][19] or, in any case, is correlated with them. Contrary to our hypothesis, the VMI skills improved to a similar extent between the two groups, although there was a statistically significant improvement within both groups in all outcome measures and high effect size.…”
Section: Discussionsupporting
confidence: 93%
“…In comparison to earlier studies primarily exploring the impact of EF training on enhancing social skills and specific EF skills [ 12 - 14 ], this study uniquely evaluates the outcomes of EF training on enhancing DLS and SI/SP [ 18 ]. Although the frequency of intervention sessions varied across studies [ 13 , 15 , 24 - 27 ], the 14-session duration in this study aligns with the current practice in pediatric OT, where definitive guidelines for intensity and frequency of treatment are currently lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A priori power analysis was conducted using G*Power 3.1.9.6 considering an effect size of 80 and a 5% margin of error based on previous studies (Kenworthy et al, 2014;Stackhouse et al, 2023). The results of the power analysis indicated that 67 participants are required to detect group differences at the β = .80 level and a 5% margin of error.…”
Section: Sample Size Determinationmentioning
confidence: 99%